PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA 2007-2011 - , FARAJ MOHAMED MIFTAH JOUHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Since the world economy is experiencing significant growth , the business world and then experiencing unprecedented growth . Ranging from national and international business . The companies that develop the pattern has a strategy and business objectives of each to be able to maintain the viability of the company . In the event that every company has a different way to make a profit , or in running the company . This is related to the company's capital . As in the company that I researched the company engaged in the food and beverage sector, listed on the IDX . These companies are able to survive since the global crisis that occurred in mid-2008 , because the support demand in the sector are quite high . To the authors wanted to examine how the impact of the liquidity and profitability of the company lavarage . In the study the authors have obtained results that negatively affect the profitability of liquidity means that the company is using more debt without increasing liquidity so that it led to decreased liquidity and negatively affect profitability also supported it because of external factors and internal , and can also be of sample needs to be added . So also with lavarage . The authors concluded that the positive effect on profitability lavarage means that the increase in external debt as defined by the company's ability to pay obligations in the future where it will be to obtain a positive response by the market . The use of debt can reduce taxable income because the company is required to pay of loan interes. Reduction can add corporate profits tax that could be used for reinvestment or for dividend distribution to shareholders . Reinvestment and dividends will increase investors' assessment so as to increase their interest to buy shares .